Stages Of Development Of The Genre Of The Short Story - Khojaeva, Raykhona (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This thesis discusses the history, development, improvement as a literary and journalistic genre, lexical meaning and content of the short story genre. Writers who created in this genre, their thoughts, and examples of short stories are presented.